Tingkat Kebugaran Jasmani Siswa Peserta Ekstrakurikuler Futsal SMA Negeri di Kabupaten Blora Tahun Ajaran 2020/2021 - Trianda Ricky Elmosta; Mohamad Annas (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of the study was to determine the level of physical fitness of students participating in futsal extracurricular at State Senior High Schools in Blora Regency for the 2020/2021 teachings.This study uses a quantitative descriptive approach. The subjects of this study were students participating in the futsal extracurricular at a State High School in Blora Regency for the 2020/2021 academic year. Total sampling of data using survey test and measurement methods. Then the data analysis technique using descriptive percentage and SPSS software version 22.The results of the study are as follows: Physical fitness level of futsal extracurricular students of SMA Negeri 1 Blora as follows, the results obtained were 1 student (1.59%) in very good category, 3 students (4.76%) in good category, as many as 51 students (80.95%) ) in the medium category, as many as 8 students (12.69%) in the less category, while students with the poor category did not exist.The conclusions from the results of the study are that: So the level of physical fitness of students participating in futsal extracurricular activities at State Senior High Schools in Blora Regency for the 2020/2021 academic year is on average in the medium category.